603 Evaluation the First Ray Instability Using the Double Dorsiflexion Test: A Prospective Observational Case-Controlled Study. (19th August 2022) - Solomou, G; Pasapula, C; Al-Sukaini, A; Liew, I; Goetz, J; Cutts, S
Abstract: First-Ray (FR) stability allows for foot propulsion in-stance, taking 60% weight. First-ray instability (FRI) is associated with middle column overload, synovitis, deformity, and osteoarthritis. Clinical detection can still be challenging. We propose to develop a clinical test that helps identify FRI using two simple manual manoeuvres. 10 patients with unilateral FRI were recruited. Stringent exclusion criteria were applied including hallux MTP pain, laxity, inflammatory arthropathy. A Klauemeter directly measured the sagittal plane dorsal first metatarsal head translation of affected vs unaffected feet. Maximum passive proximal phalanx 1 st MTP joint dorsiflexion was measured using Tracker motion software analysis with and without applying a dorsal force at the 1 st metatarsal head using a Newton meter. P-value of <0.05 was considered significant. FRI feet had dorsal translation greater than 8mm (median, 11.94; interquartile range [IQR], 10.23–13.81) vs 1.77 for unaffected control feet was (median, 1.77; interquartile range [IQR], 1.23–2.96) using the Klauemeter. The percentage reduction in 1 st MTP joint dorsiflexion ROM when applying the double dorsiflexion test FRI (mean reduction of 67.98%) when compared to control feet (mean reduction of 28.44%)(P<0.01). Receiver operating characteristic (ROC) analysis showed that a 50% reduction in dorsiflexion ROM of 1 st MTPJ when performing the double dorsiflexion test achieved a specificity of 100% and sensitivity of 90% (AUC =0.990, 95%CI [0.958–1.000], P>0.0001). The double dorsiflexion (DDF) is easy to perform with manual manoeuvres that avoid complex instrumented and radiation-based assessment. A greater than 50% decrease in proximal phalanx motion has an over 90% sensitivity in identifying feet with FRI.